2018
DOI: 10.1080/14783363.2018.1470897
|View full text |Cite
|
Sign up to set email alerts
|

Integrating QFD for product-service systems with the Kano model and fuzzy AHP

Abstract: The paper proposes a systematic procedure for the development of Product-Service Systems (PSSs) by focusing on the analysis of customer requirements, and the selection of those that can practically enhance the offerings' value. With this goal in mind, the Quality Function Deployment for Product Service Systems (QFDforPSS) method was augmented by means of the Kano model to filter the customers' needs and transform the attractive ones into Receiver State Parameters (RSPs), as the cornerstone of QFDforPSS. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 115 publications
(51 reference statements)
0
58
0
Order By: Relevance
“…In addition, the design of the business model could also benefit by taking into account customer requirements, especially as the proposed PSS model would be operating on a regulated market (such as Defence), where the customer (MoD) need to operate following public procurement rules, and it is more difficult for the end user (MoD personnel) to make purchasing decisions [69]. To minimise the impact of the PSS to the current procurement system that the MoD follows, it was suggested that the PSS used the current freight system.…”
Section: Challenges To Be Overcome For a Pss Comparison Studymentioning
confidence: 99%
“…In addition, the design of the business model could also benefit by taking into account customer requirements, especially as the proposed PSS model would be operating on a regulated market (such as Defence), where the customer (MoD) need to operate following public procurement rules, and it is more difficult for the end user (MoD personnel) to make purchasing decisions [69]. To minimise the impact of the PSS to the current procurement system that the MoD follows, it was suggested that the PSS used the current freight system.…”
Section: Challenges To Be Overcome For a Pss Comparison Studymentioning
confidence: 99%
“…To deal with the heterogeneity of DMs, AHP (Jia, Liu, Lin, Qiu, & Tan, ), Bodily's updated method (Wang, Fung, Li, & Pu, ), and fuzzy majority‐based method (Yan & Ma, ) have been developed to assign importance weights to each DM. To obtain the basic weights of ECs, objective weighting methods such as MDM (Li & He, ) and entropy‐based method (Li, Du, & Chin, ), subjective weighting methods such as AHP (Haber et al, ), analytic network process (Asadabadi, ), and BWM (Huang et al, ) have been widely used. Moreover, some researchers have viewed prioritizing the final importance ratings of ECs as a form of multicriteria decision‐making (MCDM).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent decades, QFD has been evolved as a powerful technique that assists developers in designing and developing products or services (Chan & Wu, ). Considerable researchers improved the traditional QFD by integrating with fuzzy set theory to enhance the performance of QFD (Akkawuttiwanich & Yenradee, ; Babbar & Amin, ; Haber, Fargnoli, & Sakao, ). Fuzzy linguistic methods have been applied to measure tourists' judgements to service innovation design, but their inefficient calculations were often criticized when facing vast numbers of tourists' judgements (Gomezelj, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more detail, HoQ links customer needs and expectations (the Customer Requirements (CRs)) to appropriate technical attributes (the Engineering Characteristics (ECs)) by means of a 1-3-9 score, where 1 represents a low relationship, 3 a medium relationship, and 9 a strong relationship (while a null value means no-relationship), as schematized in Figure 3. The final output is represented by the weight of ECs, as well as their relative (normalized) weight; this consequently provides grounds for their assessment and prioritization [69]. It is worth noting that in traditional HoQ, the importance level of CRs is expressed by means of a score from 1 (low importance) to 5 (high importance).…”
Section: Quality Function Deploymentmentioning
confidence: 99%